Electrospun Fe2O3-carbon composite nanofibers as durable anode materials for lithium ion batteries - Zhang, Xiang (2014)
Combination of metal oxides and carbon has been a favourable practice for their application in high-rate energy storage mesoscopic electrodes. We report quasi 1D Fe2O3-carbon composite nanofibers obtained by the electrospinning method, and evaluate them as the anode for Li ion storage. In the half-cell configuration, the anode exhibits a reversible capacity of 820 mA h g-1 at a current rate of 0.2C up to 100 cycles. At a higher current density of 5C, the cells still exhibit a specific capacity of 262 mAh g-1. Compared to pure electrospun Fe2O3 nanofibers, the capacity retention of Fe2O3-C composite nanofiber electrode is drastically improved. The good electrochemical performance is associated with the homogenous dispersed Fe2O3 nanocrystals on the carbon nanofiber support. Such structure prevents the aggregation of active materials, maintains the structure integrity and thus enhances the electronic conductivity during lithium insertion and extraction.